Ticks (Acari: Ixodidae) of northern Misiones Province, Argentina - Lamattina, Daniela; Tarragona, Evelina Luisa; Costa, Sebastián Andrés; Guglielmone, Alberto; Nava, Santiago (Systematic and Applied Acarology Society, 2019)
Information on distribution and hosts of hard ticks of northern Misiones Province in Argentina is presented in this study. Ticks were identified by morphological characters and by sequences of a 410 bp fragment of the mitochondrial 16S rRNA gene. A total of 292 ticks collected from the environment and wild and domestic mammals were identified: Amblyomma coelebs, A. brasiliense, A. dubitatum, A. incisum, A. ovale, Haemaphysalis juxtakochi and Rhipicephalus microplus. The presence of A. coelebs was confirmed for Argentina and the first record of H. juxtakochi in Misiones was presented. Some of the species as A. incisum, A. ovale and R. microplus are ticks of medical and veterinary importance. Therefore, further studies on the vectorial role of these species in Misiones Province are necessary to determine their epidemiological relevance.